Effect of an increase in coronary perfusion on transmural ventricular repolarization - Zhang, Y. Z; He, B; Wang, L. X (Physiological research, 2007)
The effect of increased coronary flow on transmural ventricular repolarization was investigated in six pentobabitalanesthetized sheep. Fresh blood at 10 ml/min was injected into the left circumflex coronary artery (LCX) in addition to the normal coronary flow. Unipolar electrocardiograms were simultaneously registered from epicardium, midmyocardium and endocardium with fine plunge needles. Activation-recovery interval (ARI) was measured from the unipolar electrocardiograms and was used for estimating the ventricular repolarization duration. It was found that intracoronary blood injection (n=3) prolonged ARI in the epicardium, mid-myocardium and endocardium by an average of 34 ± 16, 28 ± 18 and 25 ± 13 ms, respectively (p<0.01). Pretreatment with nitro-L-arginine (n=3), a nitric synthase inhibitor, diminished the flow-induced ARI prolongation across the ventricular wall. In conclusion, an increase in coronary flow lengthens the duration of transmural ventricular repolarization. These effects appear to be mediated by nitric oxide from the coronary endothelium.
Keywords: Animals; koronární cirkulace; komorová dysfunkce; krev; ovce; Blood; perfuze; Arrhythmias, Cardiac; Electrocardiography; elektrokardiografie; Coronary Circulation; Data Interpretation, Statistical; Perfusion; interpretace statistických dat; Ventricular Dysfunction; Sheep; oxid dusnatý; zvířata; Nitric Oxide; srdeční arytmie